Unmanned aerial vehicle based low carbon monitoring planning. (April 2021) - Yi, Wen; Sutrisna, Monty; Wang, Hans
Abstract: Instead of physically visiting all locations of concern by manpower, unmanned aerial vehicles (UAVs) equipped with cameras are a low-cost low-carbon alternative to carry out monitoring tasks. When a UAV flies to conduct monitoring tasks, it does not have to fly at a fixed speed; instead, it should fly at lower speeds over objects of higher concerns and vice versa. This paper addresses the UAV planning problem with a focus on optimizing the speed profile. We propose an infinite-dimensional optimization model for the problem and transform the model into a linear programming formulation based on characteristics of the problem. Our case study shows the managerial insight that the UAV flies at low speeds on important segments of the path and at its highest speeds on less-important segments. This means more durable batteries should be designed for drones that need to carry out elaborated monitoring tasks. This finding further provides guidance for drone users when purchasing and renting drones.